Identificação de crianças precoces com indicadores de altas habilidades/superdotação pelos familiares e suas expectativas - Oliveira, Elaine Cristina Batista Borges de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The family is an institution in motion in their organization, and first instance in the formation of its members. Take in the family a child early requires knowledge and ability to identify it and understand it, the manifestations of the precocity initially appear in the family context, which often do not have the necessary conditions to develop and meet the challenges of educating a child early. In this context in which early children can be a cause of family conflicts is that there is an urgent need to investigate how parents or guardians identify the precocity and what expectations have on these children. The aim of this work was to analyze how the parents and/or guardians identify precocities in their children, as well as the expectations generated in them, and check how they perceive the changes in family dynamics, in function of the precocity. This research used two questionnaires that were answered by 19 participants. The data were analyzed in two stages, the first through the analysis and discussion of the Questionnaire for the Identification of Indicators of High Abilities/Gifted - Responsible (QUIIAHSD - R) de Freitas and Perez (2012) adapted to analyze situations that would confirm the existence of indicators of precocity in the aspects of physical development, academic and social child and the second based on questionnaire responses of open questions and organized according to a content analysis of Bardin (1977), submitted from four major categories: 1. the concept of precocity; 2. moment of perception of the precocity; 3. opinion on the presence of a child early; 4. expectations. It was found that the process of identification of children with early indicators of high ability/gifted students is complex and includes many variables, but that the parents and/or guardians are also able to identify the precocity in children, regardless of daily coexistence or the knowledge you have about the subject, because they identify on the...

A família é uma instituição em movimento na sua organização, e instância primeira na formação de seus membros. Ter na família uma criança precoce requer conhecimento e habilidade para identificá-la e compreendê-la, as manifestações da precocidade aparecem inicialmente no contexto familiar, que muitas vezes não possuem as condições necessárias para desenvolver e enfrentar os desafios de se educar um filho precoce. Nesse contexto em que crianças precoces podem ser causa de conflitos familiares é que urge a necessidade de investigar como os pais ou responsáveis identificam a precocidade e quais expectativas têm sobre essas crianças. O presente trabalho teve por objetivo analisar como os pais e/ou responsáveis identificam as precocidades em seus filhos, bem como as expectativas geradas neles, e verificar como percebem as alterações na dinâmica familiar, em função da precocidade. Esta pesquisa utilizou dois questionários que foram respondidos por 19 participantes. Os dados foram analisados em duas etapas, a primeira por meio da análise e discussão do Questionário para Identificação de Indicadores de Altas Habilidades/Superdotação – Responsáveis (QUIIAHSD – R) de Freitas e Pérez (2012) adaptado para analisar situações que confirmassem a existência de indicadores de precocidade nos aspectos do desenvolvimento físico, acadêmico e social da criança e a segunda com base nas respostas do questionário de perguntas abertas e organizadas conforme a analise de conteúdo de Bardin (1977), apresentados a partir de quatro grandes categorias: 1. conceito de precocidade; 2. momento de percepção da precocidade; 3. opinião sobre a presença de uma criança precoce; 4. expectativas. Verificou-se que o processo de identificação de crianças precoces com indicadores de altas habilidades/superdotação é complexo e inclui muitas variáveis, mas que os pais e/ou responsáveis são igualmente capazes de identificar a...
Keywords: Família; Crianças superdotadas - Identificação; Educação especial; Special education